The Vulnerability of Youths Labor Market During COVID-19 Pandemic: Evidence From the Indonesia’s Labor Force Survey - Quarina, Qisha; Armadhani, Ariqoh Wahyu; Shalahuddin, Akmal; Liem, Owen Alberto (Jurnal Ekonomi Kependudukan dan Keluarga, 2024)
This study aims to investigate the youth labor market vulnerability during COVID-19 pandemic crisis in Indonesia in terms of their incidence of unemployment, duration of job search, and the probability to experience work stoppage. We utilize the Indonesian Labor Force Survey in the periods of 2019-2021, to capture the period before and during the pandemic. A descriptive analysis is used to provide an overview of the youth labor market condition before and during the pandemic. The incidence of unemployment and the job search duration analyses are investigated utilizing the probit and non-parametric Kaplan-Meier method respectively. While the probability of experiencing work stoppage during the pandemic is estimated using the multinomial logit method. This study finds supporting evidence that the youth cohort is more vulnerable than their adult counterparts, both prior and during the pandemic. Specifically, youths are more likely to experience unemployment, longer job search duration, and experience work stoppage during the pandemic crisis, particularly in 2021 when the economy suffers from the most severe pandemic situation. Results from this study are expected to contribute to the existing literature regarding youths’ labor market amidst COVID-19 crisis, particularly in preventing the potential labor market scarring of these youth workers.